2020
DOI: 10.20944/preprints202008.0519.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief Report: Rapid Clinical Recovery from Severe COVID-19 with High Dose Famotidine and High Dose Celecoxib Adjuvant Therapy

Abstract: Celecoxib as adjuvant therapy has been shown in a small randomized trial for Covid-19 to prevent clinical deterioration and rapidly improve thoracic computerized axial tomography (CT-chest)1. Multiple descriptive trials of high dose famotidine (both inpatient and outpatient) have demonstrated clinical response2,3,4. We describe the rapid clinical responses after increasing the celecoxib dosage to 400mg bid with high dose famotidine 80mg qid in both a critical inpatient who on baseline required 40 liters per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Previous pharmacological studies of famotidine have shown a dose dependent attenuation of intracellular calcium concentrations in neutrophils and at high doses that reactive oxygen species are attenuated [see Tomera and Kittah (2020b) for further details]. This would explain the clinical observations that elevated D-dimers and pulmonary emboli become responsive to standard anticoagulation therapy when given HD famotidine (Tomera and Kittah, 2020a;Radermecker et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous pharmacological studies of famotidine have shown a dose dependent attenuation of intracellular calcium concentrations in neutrophils and at high doses that reactive oxygen species are attenuated [see Tomera and Kittah (2020b) for further details]. This would explain the clinical observations that elevated D-dimers and pulmonary emboli become responsive to standard anticoagulation therapy when given HD famotidine (Tomera and Kittah, 2020a;Radermecker et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…HD famotidine for treatment of COVID-19 is now also being clinically tested in Bangladesh ( ClinicalTrials.gov Identifier: NCT04504240), and Iran ( Samimagham et al, 2020 ). Recent encouraging clinical reports include simultaneous administration of famotidine and cetirizine at standard OTC doses ( Hogan et al, 2020 ) and HD famotidine with celecoxib ( Tomera and Kittah, 2020a ; Tomera and Kittah, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…All studies included patients hospitalized with COVID-19. Three cohort studies (3,4,11) and one case series (10) included mostly patients with severe COVID-19, and one case series included patients with mild to moderate COVID-19. (5)…”
Section: Resultsmentioning
confidence: 99%
“…(11) One case series of 25 hospitalized patients with moderate disease showed zero mortality. (10) Another case series of 10 non-hospitalized patients reported improvement in patient reported outcomes. (5)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation